Pencegahan Penyakit Kulit dan Infeksi pada Nelayan melalui Praktik Personal Hygiene yang Tepat - Irma Fajriah; M. Anas; Hairudiin Hairudiin (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
Fishermen face a high risk of occupational health problems, including skin diseases and infections, due to exposure to extreme marine environments and poor personal hygiene practices in their daily work activities.3 These skin diseases can include contact dermatitis, fungal infections, bacterial infections, and other chronic skin disorders that affect fishermen's work productivity and quality of life.5 This Community Service Research aims to improve fishermen's knowledge, awareness, and skills in implementing effective personal hygiene practices through health education and practical preservation. The methods used were field observation, initial health surveys, health education, and reflection on personal hygiene practices as promotive-preventive interventions. The results showed an increase in participants' understanding of the importance of hand and body hygiene, and the care of minor wounds after the intervention. This activity was concluded to be effective and is recommended for continuous implementation for fishermen in coastal areas.